Understanding how teachers scaffold learners to make sense of biological language and concepts when using English as a mediational tool: a case study - Nakale, Elifas (Rhodes University, Faculty of Education, Department of Education, 2013)
For the past few years, Namibian grade 11-12 learners' achievement level in biology has not been very encouraging. Evidence to this effect is contained in recent examiners' reports which outline misunderstanding and various misconceptions. The causes of these misunderstandings and misconceptions may be varied, but there is credible evidence that some of it is rooted in the language problem for learners. A classroom is a social unit where many social practices are acquired, including the use of English language. Equally, it is a place where errors in language are learnt and reinforced. Triggered by these challenges facing biology learners, a qualitative case study was conducted at two secondary schools in Ohangwena Region, Namibia. Its purpose was to investigate how biology teachers scaffold learners to make sense of biological language and concepts when English is used as the mediational tool. Underpinned by an interpretivist paradigm, the study made use of document analysis, observation (lessons were also video-taped) and interviews to generate the data. Several data generating techniques were used for triangulation and validation. To further validate the data, transcripts of video-taped lessons and interviews were sent back to the research participants for member checking. The data gathering methods were also used in data presentation, analysis and interpretation to determine the extent of scaffold that teachers provide to their biology learners. The main findings of my study are that, despite efforts by participant teachers to scaffold their learners in making sense of biological language and concepts, success rates in this regard remain disappointingly low due to their (teachers) limited pedagogical content knowledge. Teachers therefore require improved mentorship, monitoring and capacity building.
Keywords: Biology -- Study and teaching (Secondary) -- Namibia Language and education -- Namibia; English as medium of instruction